Once upon a time on the air: i radiodrammi di Angela Carter (Altre Modernità, 2018)
The rewriting, often a contraposition (critical, ideological, and historical) to another text, is at the basis of Angela Carter’s dramatic works. For Angela Carter, dramatic rewriting is not the transposition of her short stories, it is not a mere adaptation to the radio, to the cinema, or to television, but a proper rewriting of her narrative material. This essay focuses on Angela Carter’s works for radio, particularly those radio plays, such as The Company of Wolves, Puss in Boots and Vampirella, whose narrative version was published in The Bloody Chamber. Carter’s radio plays are built, as she wrote, “not for creating dramas on a theatrical model so much to create complex, many-layered narratives that play tricks with time”, having in mind that the radio, like narrative, does not show, but suggests. What was fascinating to Angela Carter was the third dimension of the radio, the sound, and the shift from a  "point of view” to a “point of hearing”.